The Dynamics of Food security in Indonesia: A Study on the Availability, Affordability, and Utilization of Food in Districts and Cities with the Lowest Index in 2022 - Amalia, Siti; Siti Maria; Fitrianitha, Dessy (PT Inovasi Pratama Internasional, 2024)
In 2022, a total of 70 districts (16.83% of the total 416 districts) and 4 cities (4% of the 98 cities) were reported to have low scores in the Food security Index (FRI). This research aims to analyze the impact of the availability, affordability, and utilization of food on the Food security Index (FRI) in districts and cities with the lowest Food security Index in Indonesia. The research is quantitative with a correlational design, aiming to analyze the effect of availability, affordability, and utilization of food on the Food security Index. The study was conducted in 74 districts and cities that had the lowest Food security Index in 2022. Secondary data were obtained from the National Food Agency of the Republic of Indonesia, and data analysis was carried out using Multiple Linear Regression methods. The research findings affirm that the availability of food has a significant positive impact on the Food security Index in districts and cities with the lowest Food security Index. Meanwhile, the affordability of food also shows a significant positive influence on the Food security Index at the same local level. However, the utilization of food is not proven to have a significant impact on the Food security Index in districts and cities with low levels of food security.